2018
DOI: 10.1186/s13075-018-1600-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics approach by 1H NMR spectroscopy of serum reveals progression axes for asymptomatic hyperuricemia and gout

Abstract: BackgroundGout is a metabolic disease and is the most common form of inflammatory arthritis affecting men. However, the pathogenesis of gout is still uncertain, and novel biomarkers are needed for early prediction and diagnosis of gout. The aim of this study was to develop a systemic metabolic profile of patients with asymptomatic hyperuricemia (HUA) and gout by using a metabolomics approach, and find potential pathophysiological mechanisms of and markers of predisposition to gout.MethodsSerum samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 58 publications
2
61
1
Order By: Relevance
“…Moreover, the importance of using glucose in the profiling of a pre-disease state was stablished in another clinical trial, where healthy people and patients with different levels of T2D presented an increase on glucose concentration depending on the disease state (T2D and its complications) [28]. In addition, Zhang et al [19] aimed to identify the biomarker signature of pre-states in metabolic diseases by serum profiling with NMR. Principal components analysis and orthogonal partial least squares-discriminant analysis were used to distinguish between samples from patients and healthy controls.…”
Section: Glucosementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the importance of using glucose in the profiling of a pre-disease state was stablished in another clinical trial, where healthy people and patients with different levels of T2D presented an increase on glucose concentration depending on the disease state (T2D and its complications) [28]. In addition, Zhang et al [19] aimed to identify the biomarker signature of pre-states in metabolic diseases by serum profiling with NMR. Principal components analysis and orthogonal partial least squares-discriminant analysis were used to distinguish between samples from patients and healthy controls.…”
Section: Glucosementioning
confidence: 99%
“…Principal components analysis and orthogonal partial least squares-discriminant analysis were used to distinguish between samples from patients and healthy controls. In this study, glucose was highly expressed and included in the suggested metabolic profile for the early prediction [19]. However, taking into account the wide and easy extended use of glucometers to measure glycaemia, measure glucose levels with NMR analysis will be not justified unless additional parameters would be obtained in the same NMR profile.…”
Section: Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the metabolic differences found in this study were amino acids, which were different from previous studies. Many of the previous studies were lipid metabolites [7,9], which might be related to the inclusion criteria of our enrolled population. Adenosine is a nucleoside that is composed of adenine and D-ribose.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported the preliminary application of metabolomics in gout. Most of these studies were based on gas chromatography-mass spectrometer (GC-MS) or nuclear magnetic resonance (NMR) spectroscopy platforms [6][7][8][9]. Very few studies have applied a more sensitive metabolomics platform, ultraperformance liquid chromatography-mass spectrometry (UPLC-MS).…”
Section: Introductionmentioning
confidence: 99%